P05.30 Intracranial meningiomas: a systematic analysis of prognostic factors for recurrence in a large surgical series. (19th September 2018) - Pessina, F; Navarria, P; Carta, G; Clerici, E; Conti Nibali, M; Soffietti, R; Rudà, R; Scorsetti, M; Bello, L
Abstract: Background: Meningioma is the most common primary intracranial tumor, accounting for approximately 15–30% of primary brain tumors. About 80% are benign slow-growing meningiomas (grade I), 20% are atypical grade II meningiomas, and less than 5% are anaplastic, aggressive, grade III meningiomas. Surgical resection is the first choice of treatment. The amount of surgical resection represents a crucial factor influencing the risk of recurrence. The role of adjuvant radiotherapy (RT) is still unclear and evidence is lacking. The aim of the present study was to evaluate prognostic factors influencing the local recurrence rate in a large series of grade I-II meningiomas. Material and Methods: Newly diagnosed WHO grade I-II intracranial meningiomas underwent surgery, were included. Three different groups were defined in relation to tumor location: convexity, parasagittal, and skull base. The extent of surgical resection (EOR) was defined according to Simpson criteria, and were dichotomized as gross total resection (GTR) and subtotal resection (STR). Adjuvant RT was considered in case of STR. Clinical outcome was evaluated by neurological examination and brain MRI performed every 6 months for the first year and yearly thereafter. The 30-days postoperative morbidity and mortality were recorded. Results: From January 2000 to December 2015, 296 patients were analyzed. The majority were female (65.9%), with a KPS ≥80(94.6%), grade I meningioma(79.4%), and symptoms at diagnosis(91.5%). STR was performed in 58%, followed by adjuvant RT in 10%. Improvement or stability of neurological status was obtained in 90.4% of patients. The median follow-up time was 79 months (range 24–214 months). Local recurrence occurred in 87 (29.4%) patients at a median time of 56 months (range 6–214 months). No patients who underwent surgery plus adjuvant RT had local relapse. The median PFS was172 months(95%CI 168–188 months), and the 2, 5, 10-year PFS were 91.1%(±1.7%), 80.7%(±2.5%) and 67.2%(±3.6%), respectively. On univariate and multivariate analysis factors identified as significantly impacting PFS were the meningioma grade, the EOR, and adjuvant RT in case of STR, regardless of meningioma grade. Conclusion: Overall, our findings suggest that recurrence rates are influenced by WHO meningiomas grade, the extent of surgical resection, and the employ of adjuvant RT in not completely resected meningioma, regardless of tumor grade.